Different anaesthesia methods affect the development of hepatoblastoma after platelet activation. Issue 1 (7th January 2021) - Fei, Guoxiong; Cao, Meili; Ge, Chunlin; Xie, Yan
Abstract: This study aims to compare the influence of different anaesthesia methods on the mechanisms involved in the development of hepatoblastoma (HB). HB rabbit models were constructed and divided into three groups: disoprofol, pentobarbital sodium and HB groups. After anaesthesia, rabbit blood was collected from the tail vein. Haematological analysis (platelets) and an ELISA was used to measure the thrombopoietin (TPO) and 5‐hydroxytryptamine (5‐HT). Flow cytometry was used to determine expression of P‐selectin and PAF. The expression of 5‐HTR2B, PCNA, vWF, P70s6k, 4E‐BP1, mTOR and FRAP was determined in the tumour itself or in vascular tissues obtained from the rabbits. The platelet content in the disoprofol group. The content or expression of TPO, 5‐HT, P‐selectin, PAF, 5‐HTR2B, PCNA, vWF, P70s6k, 4E‐BP1, mTOR and FRAP was significantly higher in the disoprofol group compared to pentobarbital sodium and HB groups. Expression of these molecules was much higher in the pentobarbital sodium group compared with the HB group. These findings suggest that disoprofol anaesthesia can promote HB development via the mTOR/p70S6K1 and FRAP signalling pathway.